INFLUENCE OF WORK LIFE BALANCE AND WORK MOTIVATION ON PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE IN MILLENNIAL EMPLOYEES OF BANK SUMUT MEDAN SUKARAMAI BRANCH OFFICE - Mastura; Prihatin Lumbanraja; Yeni Absah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
In facing various challenges, companies understand that one of their greatest assets is quality of Human Resources (HR). Employees are not only expected to have superior technical skills, but to have skills and knowledge that are in line with business demands as the key to facing ever-growing competition. The existence of the Millennial generation has become the focus of attention for companies and organizations, not only because their numbers are increasing in the workplace but also because there are differences in characteristics and points of view with other generations. The aim of this research is to analyze the influence of work-life balance and work motivation on performance through job satisfaction. This research was conducted at Bank SUMUT Medan Sukaramai Branch Office with a sample of 70 respondents who were Millennial generation employees. Data were analyzed using descriptive analysis and path analysis with the Smart PLS application. The research results show that work-life balance directly has a positive and significant effect on job satisfaction, work-life balance has a positive and significant effect on performance, work motivation has a positive and significant effect on job satisfaction, work motivation has a positive and significant effect on performance, and job satisfaction has a positive and significant effect on performance. Indirectly, work-life balance has a positive and significant effect on performance through job satisfaction and work motivation has a positive and significant effect on performance through job satisfaction.